Promosi Kesehatan dengan Media Power Point dan Film Animasi Pendek dalam Upaya Pemeliharaan Kesehatan Gigi dan Mulut: Health Promotion using Power Point Media and Short Animation Films in Efforts to Maintain Dental and Oral Health - Damayanti, Siti; Brahmastha, Fathir; Salsabillah, Sausan (Journal of Public Health Education, 2022)
Background: Oral and dental health is important in the life of every individual, including children, because damaged and untreated teeth will cause pain, and mastication disorders and can interfere with other body health. One of the most common dental health problems in children is dental caries. Dental disease is a very disturbing problem in school children because it not only causes pain but also transmits infections to other parts of the body, resulting in decreased productivity. This condition will certainly reduce the frequency of children's attendance at school, interfere with learning concentration, and affect appetite and food intake so that it can affect nutritional status. Objectives: To find out how the students of TPA Miftahul Jannah, Kota Depok in 2021 know about dental and oral health, determine priority issues and carry out effective health promotion. Method: This research is a study to find out the problem points in dental and oral health and carry out appropriate health promotion. The population in this study were TPA Miftahul Jannah students, Depok City in 2021 with a sampling technique, namely a total sampling of 30 respondents. The data collection used is the researcher's interview with the interview question sheet to the respondents. Determination of priority problems using the Criteria Matrix Technique. Results: Results Based on research from 30 respondents from Miftahul Jannah TPA students in Depok-West Java, as many as 16 respondents (53.3%) had never checked their teeth every 6 months for the last 1 month. This is due to a lack of knowledge about the importance of maintaining dental and oral health. Conclusion: It was concluded that the priority problem point was never having a dental check-up every 6 months related to oral health maintenance. So the health promotion that the researchers did was the use of powerpoint slides and videos to effectively increase respondents' knowledge, which was marked by increased motivation and behavior to maintain dental hygiene.